Languages in Contact - Some Results of Research at Albanian University Students in Italy - Prendushi, Gjilda Alimhilli (European Journal of Multidisciplinary Studies, 2017)
This work is the result of personal observations of university Albanian students` studying Albanian language, with different times of residence in Italy, and contact between the Albanian and Italian language, too. My contacts with the students are grouped in two situations: those at work as lectures, seminars, receptions and examinations, and casual. It can be seen big differences in the use of two languages in these different situations. In the first group, at work, the use of the Albanian language is certainly much more correct and various forms of "mixing" almost non-existent. In the second group, especially among people very close or in the presence of Italian friends, it can be seen immediately code changes between Albanian and Italian. The communication code changing is under the influence of various factors. It is clear that reference students use Italian for formal use, for example, in their communications with teachers, while the Albanian in informal situations as at home and more. Thus, the choice of language is influenced by situational factors, like the stylistic choices that people make in a single language. Moreover, they with the language choice can move and change the tone of a situation, from formal to informal, too. These situations encountered made the basis for beginning the study. The examples cited in this paper are collected and classified, in accordance with the standard methodology, into various groups according to the probable cause for the change of the code of communication: Code changes used mainly in Italy but also in Albania; Code changes related to technology; Code changes related to the pronunciation; Code changes related to the characteristics of the country where they stay; Translations. Certainly, this first phase of research has shown the clear presence of code changes in the Albanian language. These phenomena are of various types and of varying importance: in a group of individuals it is a strong influence of the territory, Italy, for this reason we can presume that, back in Albania, the students will lose it; in another group of individuals it seems that it could turn, maybe, into loans. The last category includes some words that reflect deficiencies in the lexicon of the Albanian language, but also others that may gain ground thanks to their peculiarities. The results presented in this work should not be generalized, they only aspire to expand our understanding to the linguistic and social phenomena of contact between two languages such as Albanian and Italian, and in general, on the subject of bilingualism and the effects of the stay for a long time in Italy of Albanian people.
Keywords: Languages in Contact - Some Results of Research at Albanian University Students in Italy